What have we really learned? Twenty five years after Piper Alpha. Issue 1 (27th June 2014) - Broadribb, Michael P.
<x xml:space="preserve">Abstract</x> Twenty five years ago, a major disaster in the North Sea took the lives of 165 persons on board the Piper Alpha oil production platform as well as 2 people from the rescue crew. To this day, the incident represents the worst offshore oil industry disaster ever and has become an industry‐changing watershed event. The subsequent Public Inquiry report made a number of recommendations that were related to inherently safer design (ISD), including the mandatory use of a systematic fire and explosion analysis, analysis of smoke and gas ingress to living quarters, and the requirement for a temporary (safe) refuge area capable of surviving the initial fire/explosion. Other recommendations addressed analysis of the vulnerability of safety critical equipment/elements, and evacuation, escape, and rescue in the event of major incidents. Implementation of the above recommendations aimed to reduce the residual risk of the design through the use of an ISD approach. The residual risk then had to be managed by a safety management system (SMS), which is another inquiry recommendation that comprises many of the elements of process safety. Finally, the inquiry recommended developing a Safety Case to describe and justify the design, the inherent hazards and residual risk, and the SMS. This Safety Case is now the basis for periodic audits. Over the past 25 years this author has had the opportunity to visit offshore production platforms and drilling rigs and to review new offshore projects in many regions of the world. This article addresses both the strengths and weaknesses observed, and a number of common themes involving management systems, human factors, process safety and integrity management at such facilities. Comparisons will be drawn to the evidence aimed at preventing future major incidents that the author and others presented at the Piper Alpha Inquiry, and to the Inquiry recommendations. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 16–23, 2015